Enterprise application development with Visual C++ 2005 - Fomitchev, Max (Charles River Media, 2007)
Enterprise Application Development with Visual C++ 2005 teaches developers how to create practical business applications using managed C++ and Visual Studio? 2005. It offers best practices for coding and C++ development, including class programming, code factoring, source control, memory management, and interdependency and interoperability. Special attention is also given to new features in Visual C++ 2005, such as IDE enhancements, compiler features, ECMA syntax for managed C++, and C++ language extensions. Database application development, XML Web Service integration, and MSI deployment tools integrated in Visual Studio 2005 are also covered in detail. Throughout the book a wide variety of practical examples are used to illustrate features of the language. In addition, users learn how to create an enterprise application installation package from the ground up, which performs a full range of deployment tasks ranging from creating SQL Server database to registering and configuring both managed and unmanaged Windows and XML Web Services. After reading this detailed resource, developers and programmers will have all the skills needed to create enterprise-quality applications